Numerical simulation of non-uniform suspended sediment flowing into the Yangtze River Estuary, China based on a river network model - Ge, Hua; Zhu, Lingling; Mao, Bing (Frontiers in Marine Science, 2024)
The non-uniform suspended sediment flowing into the Yangtze River Estuary (YRE) has a substantial impact on riverbed evolution and the ecological environment. Conducting a numerical simulation can provide missing measurement data and act as an important support for river management. In this study, we developed a formula for determining the non-uniform suspended sediment-carrying capacity (SCC) based on the statistical theory of sediment transport. The formula was applied to a river network model domaining the tidal section of the lower reaches of the Yangtze River (LYR) to simulate the non-uniform suspended sediment flowing into the YRE. The verification results showed that the model accurately simulated fine-grained sediments with a high measurement accuracy. The simulation results for coarse-grained sediments were consistent with riverbed evolution that manifests as erosion. Owing to the sediment transport complexity in natural rivers, we propose a method for optimizing calculations of the SCC that provides more accurate modeling results and can be adapted when the observational measurement accuracy is improved in the future. These findings provide support for simulations and measurements of non-uniform suspended sediment transported in the LYR.